The Concept of Adabul Alim Wal Muta'alim Viewed from the Professional Ethics of the Teacher: Konsep Adabul Alim Wal Muta'alim Ditinjau Dari Etika Profesi Guru - Farnidah, Rifdah; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to explore moral education through the book adabul alim wal muta'alim written by KH. Hasyim Asy'ari and the ethics of the teaching profession, so that from an understanding of moral education and professional ethics, teachers can vary and look perfect. The research approach used is library research, the data obtained from a literature review with a factual historical approach. The results of the study found that in the moral education written by KH.Hasyim Asy'ari and the professional ethics of the teacher, it contained moral values, personal character of a teacher, teacher's morals to students, and teacher's morals in teaching. Where both of them have the same meeting point and meaning even though the discussion is different.